Minutes of the third annual delegates' conference held on Sunday, 7th October 1972 Minutes of the special delgates' conferene held on Sunday, 14th July, 1963. And, Report of the executive council (Amalgamated Union of Public Employees, 1963)
Title in English and Malayan. Stencil.